Assessing the Validity and Reliability of a Questionnaire on Dietary Fibre-related Knowledge in a Turkish Student Population (Journal of Health, Population and Nutrition, 2014)
This study aimed to validate a questionnaire on dietary fibre (DF)-related knowledge in a Turkish student population. Participants (n=360) were either undergraduate students who have taken a nutrition course for 14 weeks (n=174) or those in another group who have not taken such a nutrition course (n=186). Testretest reliability, internal reliability, and construct validity of the questionnaire were determined. Overall internal reliability (Cronbachs alpha=0.90) and test-retest reliability (0.90) were high. Significant differences (p